2020
DOI: 10.1186/s13643-020-01382-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the usefulness of evidence concerning the effectiveness of implementation strategies for knowledge products in primary healthcare: protocol for a series of systematic reviews

Abstract: Background: The literature on the implementation of knowledge products is extensive. However, this literature is still difficult to interpret for policymakers and other stakeholders when faced with choosing implementation strategies likely to bring about successful change in their health systems. This work has the particularity to examine the scope of this literature, and to clarify the effectiveness of implementation strategies for different knowledge products. Consequently, we aim to (1) determine the streng… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The protocol of the project was registered on the Open Science Framework platform on February 7, 2020 [ 26 ] and then published [ 27 ]. The review was conducted following the Cochrane methodology [ 28 ] and is reported in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The protocol of the project was registered on the Open Science Framework platform on February 7, 2020 [ 26 ] and then published [ 27 ]. The review was conducted following the Cochrane methodology [ 28 ] and is reported in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…We focused on implementation strategies that were predetermined in our protocol [ 27 ] and based on the Effective Practice and Organization of Care (EPOC) [ 8 ] to include the following implementation strategies: audit, feedback, audit and feedback, clinical incident reporting, monitoring the performance of the delivery of health care, communities of practice, continuous quality improvement, educational games, educational materials, educational meetings, educational outreach visits or academic detailing, clinical practice guidelines, interprofessional education, local consensus processes, local opinion leaders, managerial supervision, patient-mediated interventions, public release of performance data, reminders, routine patient-reported outcome measures, and tailored interventions. A review may have included primary studies that use exclusively 1 type of implementation strategy (mono-faceted) or exclusively more than 1 type (multifaceted).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These different sources of information are often summarised and combined to create ‘knowledge products’ that aim to support behaviour change. Examples of knowledge products include clinical practice guidelines, standards, policies, guides and casebooks, all of which offer guidance to healthcare providers (HCPs) (Zomahoun et al, 2020). The availability of these products, however, does not mean that they are systematically implemented into clinical practice (Zomahoun et al, 2020), which limits the potential for patients to benefit from EBP (Fernandez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of knowledge products include clinical practice guidelines, standards, policies, guides and casebooks, all of which offer guidance to healthcare providers (HCPs) (Zomahoun et al, 2020). The availability of these products, however, does not mean that they are systematically implemented into clinical practice (Zomahoun et al, 2020), which limits the potential for patients to benefit from EBP (Fernandez et al, 2019). Implementation challenges include individual‐level factors, such as lack of information and demanding clinical workload, and organisation‐level factors, such as lack of resources and leadership support (Parmar et al, 2022; Warren et al, 2016).…”
Section: Introductionmentioning
confidence: 99%